Preoptic Area Modulation of Arousal in Natural and Drug Induced Unconscious States - Reitz, Sarah L.; Kelz, Max B. (Frontiers in Neuroscience, 2021)
The role of the hypothalamic preoptic area (POA) in arousal state regulation has been studied since Constantin von Economo first recognized its importance in the early 20th century. Over the intervening decades, the POA has been shown to modulate arousal in both natural (sleep and wake) as well as drug-induced (anesthetic-induced unconsciousness) states. While the POA is well known for its role in sleep promotion, populations of wake-promoting neurons within the region have also been identified. However, the complexity and molecular heterogeneity of the POA has made distinguishing these two populations difficult. Though multiple lines of evidence demonstrate that general anesthetics modulate the activity of the POA, the region’s heterogeneity has also made it challenging to determine whether the same neurons involved in sleep/wake regulation also modulate arousal in response to general anesthetics. While a number of studies show that sleep-promoting POA neurons are activated by various anesthetics, recent work suggests this is not universal to all arousal-regulating POA neurons. Technical innovations are making it increasingly possible to classify and distinguish the molecular identities of neurons involved in sleep/wake regulation as well as anesthetic-induced unconsciousness. Here, we review the current understanding of the POA’s role in arousal state regulation of both natural and drug-induced forms of unconsciousness, including its molecular organization and connectivity to other known sleep and wake promoting regions. Further insights into the molecular identities and connectivity of arousal-regulating POA neurons will be critical in fully understanding how this complex region regulates arousal states.